Correlation of subjective and objective assessment of hypernasality in children with repaired cleft lip and palate - K S Girish; M Pushpavathi (Wolters Kluwer Medknow Publications, 2021)
Introduction: Correlational studies between subjective and objective evaluations in the area of cleft lip and palate might provide evidence on the reliability and validity of subjective evaluations. This will, in turn, help in deciding to use subjective evaluations in remote areas. Such correlational studies are scanty in Indian languages. Aims: The present study aimed at correlating the perceptual rating of hypernasality with its instrumental measure in Kannada speaking children with repaired cleft lip and palate (RCLP) across different stimuli. The study also discusses various aspects that affect nasality (the type of speech stimuli and age of first palatal surgery) which helps in better understanding of RCLP cases and their characteristics. Settings and Design: This study was based on correlational research designs. Subjects and Methods: Twenty-three Kannada speaking children with RCLP served as participants. Speech samples (vowels, oral words, nasal words, oral sentences, nasal sentences, and oronasal sentences) of children with RCLP were recorded using a sound level meter and were perceptually evaluated using Henningsson's rating scale by three experienced speech-language pathologists. Furthermore, nasalance values were objectively obtained using a nasometer. Statistical Analysis: This study was statistically analyzed using the Shapiro-Wilk test of normality and Spearman's correlation. Results: The results revealed a high positive correlation (0.78) between the subjective and objective assessment. The different degrees of perceptually rated hypernasality were in a positive correlation with nasometry scores of vowels (0.766), words (0.785), and sentences (0.819). Conclusions: A good correlation was obtained between the subjective and objective measurement of nasality indicating the high utility of perceptual evaluation in remote areas.